Distinct Impacts of Carbon Dioxide Removal and Radiation Management on Regional Monsoons - Qi Zuo; Jian Cao; Mengying Zhao (International Journal of Climatology, 2026)
Global mean surface temperature has gradually risen, with warming approaching 1.5°C over the past 3 years. To mitigate or offset global warming, the temperature mitigation approaches of carbon dioxide removal (CDR) and several radiation management (RM) approaches have been proposed. Studies have demonstrated the spatial heterogeneity of rainfall responses to individual temperature mitigation approaches. However, a detailed comparison of monsoon responses across regions and approaches is still lacking. This study investigates the impacts of the global‐scale CDR and four RM approaches on the monsoons using the Community Earth System Model. Results show that global cooling reduces monsoon rainfall over Asia and the Southern Hemisphere, but increases North American monsoon rainfall in our simulations. In contrast, the North African monsoon response depends on the specific temperature mitigation approach. The CDR reduces North African rainfall, whereas RM approaches increase it to varying degrees. Moisture budget analysis indicates that the thermodynamic effect reduces monsoon rainfall globally, whereas the dynamic effect is both region‐ and approach‐dependent. The increased North American monsoon rainfall is attributed to enhanced monsoon circulation driven by the sea surface temperature gradient between the southeastern Pacific and the North Atlantic. The approach‐dependent changes in North African rainfall are primarily governed by differences in lower‐ and mid‐tropospheric monsoon circulation. Our findings suggest that the temperature mitigation may bring dual benefits of cooler temperature and increase freshwater resources for North American, but pose challenges for climate mitigation efforts in North Africa.